Three-dimensional numerical modeling for assessing airborne infection risk in hospital waiting rooms with various ventilation approaches - Kewalee Suebyat; Nopparat Pochai; Jenjira Sooknum; Pravitra Oyjinda (Modeling Earth Systems and Environment, 2026)
Abstract Airborne infectious diseases, such as COVID-19, TB, MERS, and SARS, constitute a profound threat to public health and quality of life. These pathogens are transmitted primarily via atmospheric particles, especially within clinical environments, where they often circulate. Effective ventilation controls to mitigate pathogens and air pollution are thus essential for reducing hospital-based transmission of airborne infections. The purpose of this research is to assess the risk of airborne infectious diseases within a hospital in Thailand using a mathematical model. Specifically, the finite difference technique is employed to estimate carbon dioxide (CO 2 ) concentration as a proxy for indoor air quality to indicate and assess the risk of airborne infectious diseases. The hospital layout is categorized into waiting areas and circulation areas with disparate occupant densities. Three simulation scenarios are conducted, accounting for variations in ventilation rates and architectural structure of hospitals. The results of this research demonstrate that CO 2 concentration can be effectively quantified as a proxy for indoor air quality within hospital environments. These calculated CO 2 levels are subsequently used to model the risk of airborne infection at a hospital, providing a robust framework for assessing this risk. Crucially, by integrating ventilation dynamics that reflect the physical constraints and structure of the hospital, this research enables precise evaluation of infection risks. The findings indicate that ventilation control can reduce the incidence of airborne infection, with significant practical utility in real-world clinical settings.
Keywords: Infection Control and Ventilation; Indoor Air Quality and Microbial Exposure; Healthcare Facilities Design and Sustainability